1996
DOI: 10.1071/ea9960633
|View full text |Cite
|
Sign up to set email alerts
|

Production and composition of milk by dairy cows fed common vetch or lupin grain as protein supplements to a silage and pasture-based diet in early lactation

Abstract: Milk production and composition were measured for 49 days in early lactation in 40 Holstein-Friesian cows fed 8 kg/day (fresh weight) of 1:1 mixtures of either rolled barley-lupin grain (Lupinus angustifolius L. cv. Gungurru) or barley-common vetch grain (Vicia sativa L. cv. Blanche Fleur). All cows were fed 1 kg/day of a pelleted concentrate containing minerals and vitamins, and wilted perennial ryegrass-subterranean clover pasture silage was available ad libitum with restricted grazing of perennial ryegrass-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Valentine and Bartsch (1996) found that milk, fat and protein yield were higher for cows fed barley/blue lupins than for those fed barley/ vetch. Froidmont and Bartiaux-Thill (2004) found that coarsely ground white lupins could efficiently replace soybean meal on an N basis in high-producing dairy cow feed without any loss of milk production.…”
Section: Type Of Supplement Feed: Lupins or Soybeans Versus Cerealsmentioning
confidence: 93%
“…Valentine and Bartsch (1996) found that milk, fat and protein yield were higher for cows fed barley/blue lupins than for those fed barley/ vetch. Froidmont and Bartiaux-Thill (2004) found that coarsely ground white lupins could efficiently replace soybean meal on an N basis in high-producing dairy cow feed without any loss of milk production.…”
Section: Type Of Supplement Feed: Lupins or Soybeans Versus Cerealsmentioning
confidence: 93%
“… Supporting literature: Hadjipanayiotou et al., ; Aguilera et al., ; Aletor et al., ; Valentine and Bartsch, ; Abreu and Bruno‐Soares, ; Darre et al., ; Allan et al., ; Hadjipanayiotou and Economides, ; Farran et al., ; Collins et al., , ; González and Andrés, ; Sharma and Kalia, ; Rotger et al., ; Mikić et al., ; Samarah and Ereifej, ; Budag and Bolat, ; Ramos‐Morales et al., ; Larbi et al., ; Uzun et al., ; Seifdavati et al., ; Mao et al., ; Rybiński et al., . …”
Section: Nutritional Composition Of the Common Vetchmentioning
confidence: 99%
“…The gross energy (GE) content of common vetch seeds is 17.10–21.10 MJ/kg DM (Hadjipanayiotou et al., ; Abreu and Bruno‐Soares, ; Ramos‐Morales et al., ), while the metabolizable energy (ME) content is 8.67–12.50 MJ/kg DM (Valentine and Bartsch, ; Budag and Bolat, ).…”
Section: Nutritional Composition Of the Common Vetchmentioning
confidence: 99%
“…Compared with other legumes, common vetch exhibits high concentrations of crude protein between 93 24 to 32% (Francis et al, 2000) and carbohydrates and fiber are comparable to that of lupin (Valentine 94 and Bartsch, 1996). Common vetch seeds contain eighteen amino acids and the ratio of essential amino 95 acids/non-essential amino acids is about 0.7 (Mao et al, 2015) which is significantly higher than the 96 0.38 recommended by WHO (Who, 2007).…”
Section: Common Vetch Seeds: Important Nutritional Attributes 80mentioning
confidence: 86%
“…Obstructing the development of the higher value product is a range of anti-nutritional factors, the 104 most significant of which are the dipeptide γ-glutamyl-β-cyanoalanine (GBCA) and the free amino 105 acid β-cyano-L-alanine (BCA), that exist in relatively high concentrations in the seed at approximately 106 2.6% and 0.9%, respectively (Tate et al, 1999). Such compounds are toxic to monogastric species, 107 such as chickens or pigs, but have no obvious effect upon ruminant species, including beef cattle 108 (Valentine and Bartsch, 1996). In addition, vicine, convicine, and other anti-nutritional factors typical 109 of leguminous crops, including tannins, trypsin inhibitors and polyphenols are also present.…”
Section: Common Vetch Seeds: Important Nutritional Attributes 80mentioning
confidence: 99%